Motivation of Thai Generation Y Tourists Towards Gastronomy Tourism In San Sai District Area Chiangmai Province: Motivation of Thai Generation Y Tourists Towards Gastronomy Tourism In San Sai District Area Chiangmai Province - Sittajarn, Wanrapa; Sirivistkul, Saint; Thamchalai, Anan (RATANABUTH JOURNAL, 2024)
The objective of this research were to: 1) study the level of motivation for food tourism among Generation Y tourists in San Sai District, Chiang Mai Province; 2) compare the motivation for food tourism among Generation Y tourists in San Sai District, Chiang Mai Province, based on personal characteristics; and 3) compare the motivation for food tourism among Generation Y tourists in San Sai District, Chiang Mai Province, based on tourism behavior. Data were collected from Generation Y tourists who visited 16 restaurants participating in the Lanna Food Culture Project with San Sai Subdistrict Municipality, Chiang Mai Province, through an app, with a total of 400 respondents. The statistical methods used for data analysis included mean, standard deviation, t-test, and F-test. The research findings indicated that the overall motivation for food tourism among Generation Y tourists in San Sai District, Chiang Mai Province, was at a high level. When examining specific aspects, it was found that motivation related to pull factors was higher than motivation related to push factors. The hypothesis testing revealed that: 1) the motivation for food tourism among Generation Y tourists in San Sai District, Chiang Mai Province, did not differ based on personal characteristics; 2) the motivation for food tourism among Generation Y tourists in San Sai District, Chiang Mai Province, differed based on tourism behavior, with significant differences observed in terms of tourism experience and tourism patterns at the .05 level